Estrogen Regulates Ca2+ to Promote Mitochondrial Function Through G-Protein-Coupled Estrogen Receptors During Oocyte Maturation - Qingyang Liu; Jingmei Li; Yanxue Li; Ming Cheng; Hui Zhang; Baohua Ma (Biomolecules)
Estrogen is a steroid hormone that plays a key role in regulating many physiological processes, such as follicle activation and development and oocyte maturation in mammals. Ca2+ is crucial in oogenesis, oocyte maturation, ovulation, and fertilization. However, the mechanism by which estrogen regulates Ca2+ during oocyte maturation in mice has not been reported. This study revealed that Ca2+ levels in oocytes significantly increase during the 4–12 h period in vitro. Oocytes treated with 0.1 µM estrogen and 1 µM G1, a G-protein-coupled estrogen receptor (GPER) agonist, showed significantly increased Ca2+ levels, while treatment with 1 µM G15, an antagonist of GPER, significantly decreased Ca2+ levels. Notably, estrogen regulates Ca2+ in oocytes through the GPER pathway and promotes the expression of the Ca2+-producing protein EPAC1. In addition, estrogen alleviates the inhibitory effect of the Ca2+ chelator BAPTA-AM during oocyte maturation by promoting Ca2+ production. Furthermore, estrogen can promote the expression of the mitochondrial generation-associated protein SIRT1 through the GPER pathway, alleviate mitochondrial oxidative damage caused by BAPTA-AM, and restore the mitochondrial membrane potential level. Collectively, this study demonstrates that estrogen can regulate Ca2+ through the GPER-EPAC1 pathway and promote the expression of SIRT1, which promotes oocyte mitochondrial function during oocyte maturation.